2011
DOI: 10.1177/0143034311418912
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of various degrees of vocational secondary school absenteeism: Importance of the organization of the educational system

Abstract: The aim of this research was to study different types of absenteeism in vocational secondary school taking into account the specificity of the school context. Participants were 523 students. First, three school absenteeism groups were established: Students with no absenteeism (nearly 64% of the sample), students with absenteeism (26%), and students with problematic absenteeism (10%). These groups were then compared according to four dimensions directly linked to the school context in order to identify the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…In the literature, there are many definitions within the scope of absenteeism. For example, Lannegrand-Willems et al (2012) defined absenteeism as, "a student being absent in school with or without an excuse". Robinson (2009) considered absenteeism by describing behavior and defined it as "not attending the school with or without an excuse, miss some classes or being late for class".…”
Section: Definition Of the Concept Of Absenteeismmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, there are many definitions within the scope of absenteeism. For example, Lannegrand-Willems et al (2012) defined absenteeism as, "a student being absent in school with or without an excuse". Robinson (2009) considered absenteeism by describing behavior and defined it as "not attending the school with or without an excuse, miss some classes or being late for class".…”
Section: Definition Of the Concept Of Absenteeismmentioning
confidence: 99%
“…Focusing on absenteeism as a problem, the duration is as important as the type of absenteeism. As Lannegrand-Willems et al (2012) indicated, when absenteeism is rare, it is not considered to indicate a problematic situation. However, increased absenteeism is considered to be an indicator of various risk factors.…”
Section: Definition Of the Concept Of Absenteeismmentioning
confidence: 99%
See 2 more Smart Citations
“…El cuestionario, diseñado ad hoc para este estudio, está basado fundamentalmente en el modelo de asociación entre contexto (familia, padres, escuela, comunidad), implicación (cognitiva, comportamental, emocional) y resultados del alumnado de Reschly y Christenson (2012), y en la revisión de distintos instrumentos para su medición. Destacan aquí las aportaciones del Student Engagement Instrument (SEI), utilizado en el proyecto Check&Connect (Appleton, 2012); del kit de evaluación de abandonos potenciales (Trousse d'évaluation des décrocheurs potentiels-TEDP), utilizado en Quebec (Janosz, Archambault, Lacroix y Lévesque, 2007), y de un estudio sobre absentismo en educación secundaria profesional en Francia (Lannegrand, Cosnefroy y Lecigne, 2012).…”
Section: Instrumentounclassified